Effect of distinct drying approach on bioactive compounds and nutritional profiling of Ulva intestinalis and Padina tetrastromatica from the Bay of Bengal, Bangladesh - Abu Bakker Siddique Khan; Md. Rahamat Ullah; Mousumi Akhter; Md. Monjurul Hasan; Farhana Yasmin; Aovijite Bosu; Mohammed Ashraful Haque; Md. Mohidul Islam; Al-Amin; Md. Amirul Islam; Md. Zulfikar Ali (Food Chemistry Advances)
Marine algae have been visualized as fostering a prevalent actuation of bioactive substances that have noteworthy therapeutic effects. The current investigations deployed a trio of separate drying methods, i.e., oven drying, freeze drying, and sun drying, to quantify the total phenolic content (TPC), total flavonoid content (TFC), and dietary vitality of Ulva intestinalis and Padina tetrastromatica. By mining and scrutinizing it to the quercetin and gallic acid standards, TPC and TFC were derived. Among three drying techniques, freeze drying asserted higher TPC (12.59 ± 1.07 in U. intestinalis and 68.74 ± 1.95 mg of GA/g in P. tetrastromatica) and TFC (7.92 ± 0.97 in U. intestinalis and 58.15 ± 2.05 mg of quercetin/g in P. tetrastromatica) values. Ulva intestinalis and P. tetrastromatica also contain a high amount of protein (18.34% and 8.7%, respectively). The findings demonstrated that green seaweed possessed higher levels of potassium (2.20%) and molybdenum (2.41%) and brown seaweed showed higher amounts of potassium (2.41%) and calcium (1.11%). Where rapid drying methods are recommended to enhance constituent levels, freeze-drying could be an attractive alternative to oven and sun drying, as it addresses the drawbacks associated with prolonged drying periods.